Effectiveness of a Counseling Package Based on the Prevention of Academic Procrastination on Learning Behaviors, Academic Self-Regulation, and Academic Resilience - Karevan Brojerdi , Kiyana; Shariat Bagheri, Mohammad Mahdi; Salehi, Keyvan (International Journal of Education and Cognitive Sciences, 2026)
Purpose: The purpose of this study was to evaluate the effectiveness of a counseling package based on students’ lived experiences for preventing academic procrastination and improving learning behaviors, academic self-regulation, and academic resilience among female lower secondary school students. Methods and Materials: This quasi-experimental study employed a pretest–posttest–follow-up design with a control group. The sample included 60 female lower secondary school students from Tehran, who were equally assigned to experimental and control groups. The intervention consisted of 12 counseling sessions lasting 60–90 minutes each, focusing on various aspects of behavior, cognition, communication, motivation, and emotion. Data were collected using validated scales for learning behaviors, academic self-regulation, and academic resilience, and were analyzed using SPSS version 26 with descriptive statistics and repeated measures analysis of variance. Findings: The results of the analysis of variance indicated that the experimental group showed significant improvement compared to the control group (p < .01). The Bonferroni post-hoc test revealed increases in learning behaviors and their components, self-regulation and its components, and resilience in the posttest (p < .01). Moreover, these effects were sustained at follow-up (p < .05). Conclusion: The counseling package based on students’ lived experiences effectively enhanced academic skills and resilience. This approach can be integrated into educational programs to help students overcome procrastination, achieve better academic performance, and improve mental health.